Control of Carbon Dioxide Bivalent Heat Pump on Heating of Buildings - Sit M.L.; Juravleov A.A.; Frid S.E.; Timchenko D.V. (Problems of the Regional Energetics)
The scheme of a bivalent heat pump (BHP) is considered, using both the heat of the water from the return network and the heat of the outside air as low-potential heat sources (LPH). The aim of the work is to create a BHP circuit that provides functioning at the variable heat load temperature. The goal was achieved by solving the following problems: analysis of methods of synthesis of BHP circuits, analysis of circuit operation under random disturbances and development of the automatic control systems for BHP. The most significant result of the work is: a heat pump circuit that can operate at variable pressures of the evaporator and the gas cooler. The next significant result is, for bivalent heat pumps intended for operation in heat supply systems with qualitative and qualitative-quantitative laws of thermal control, the introduction into the heat pump circuit of a heat exchanger installed in the return water circuit of the secondary building and cooled by outside air, as well as two control valves installed in series between the gas cooler and the evaporator, the first valve installed along the refrigerant flow being controlled by a signal based on the pressure difference between the outlet of the gas cooler and the separation vessel between the evaporator and the gas cooler, and the second by pressure in front of the evaporator. The significance of the obtained results lies in the increase of the COP of the heat pump, due to the increase of heat transfer in the gas cooler circuit. The HHP circuit differs from the known ones in that it uses two control valves and the heat exchanger for additional cooling of the return water of the BHP heated building.